2021
DOI: 10.3847/2041-8213/ac004a
|View full text |Cite
|
Sign up to set email alerts
|

Supernova Luminosity Powered by Magnetar–Disk System

Abstract: Magnetars are one of the potential power sources for some energetic supernova explosions such as type I superluminous supernovae (SLSNe I) and broad-lined type Ic supernovae (SNe Ic-BL). In order to explore the possible link between these two subclasses of supernovae (SNe), we study the effect of fallback accretion disk on magnetar evolution and magnetar-powered SNe. In this scenario, the interaction between a magnetar and a fallback accretion disk would accelerate the spin of the magnetar in the accretion reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…For such high fallback rates, the accretion flow is likely able to penetrate and squeeze the proto-neutron star magnetosphere, causing an initial phase of direct accretion onto the surface. This might also result in the burial of the magnetic field (see for example Taam & van den Heuvel 1986;Li et al 2021;Lin et al 2021), a scenario that (combined with the subsequent secular re-emergence of the magnetic field) has been invoked to explain the observed properties of Central Compact Objects (CCOs) (Halpern & Gotthelf 2010;Fu & Li 2013;Ho 2015;Zhong et al 2021); a class of young, generally weak-field neutron stars found close to the centers of supernova remnants. After this initial direct accretion phase, as the fallback rate decreases in time, the neutron star could enter a propeller phase that could cause the star to spin-down as in the disk scenario.…”
Section: Accretion From Spherical Fall-backmentioning
confidence: 99%
“…For such high fallback rates, the accretion flow is likely able to penetrate and squeeze the proto-neutron star magnetosphere, causing an initial phase of direct accretion onto the surface. This might also result in the burial of the magnetic field (see for example Taam & van den Heuvel 1986;Li et al 2021;Lin et al 2021), a scenario that (combined with the subsequent secular re-emergence of the magnetic field) has been invoked to explain the observed properties of Central Compact Objects (CCOs) (Halpern & Gotthelf 2010;Fu & Li 2013;Ho 2015;Zhong et al 2021); a class of young, generally weak-field neutron stars found close to the centers of supernova remnants. After this initial direct accretion phase, as the fallback rate decreases in time, the neutron star could enter a propeller phase that could cause the star to spin-down as in the disk scenario.…”
Section: Accretion From Spherical Fall-backmentioning
confidence: 99%
“…Comparing to stellar fragment fallback determined accretion (e.g., Lin et al 2021), the MHD instability induced periodic accretion process have a shorter time interval for two successive accretion, for this scenario, the inner disk ram pressure can be released timely. Furthermore, the observed periodic accretion process may imply the disk has reached a quasi-steady state (The disk may erratic when it born in the collapse of a massive star).…”
Section: Conclusion and Discussionmentioning
confidence: 88%
“…A corotating magnetosphere of the magnetized NS preventing the plasma accretion and throwing away the accreting materials were figured as propeller (Illarionov & Sunyaev 1975;Campana et al 1998). A competing process of accretion and propeller was figured in the recent studies (e.g., Eks ¸i et al 2005;Gompertz et al 2014;Lin et al 2021). However, the coexistence of accretion and outflow was also suggested by some of the magnetohydrodynamic (MHD) simulative studies (e.g., Goodson et al 1997;Romanova et al 2005Romanova et al , 2009Romanova et al , 2018Ustyugova et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…After fallback accretion has slowed, the magnetar would subsequently spin down via the propellor mechanism and/or dipole radiation, driving a type Ic-BL SN. In this scenario, Ic-BL can be produced by events with large magnetic fields of B ∼ 10 15 G and short fallback times of t fb ∼ 100 s, while SLSNe Ic can be produced by events with lower magnetic fields of B ∼ 10 14 G and long fallback times of t fb ∼ 10 4 s (Lin et al 2020(Lin et al , 2021.…”
Section: Magnetar Central Enginesmentioning
confidence: 99%